2011
DOI: 10.1016/j.jcin.2010.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Inhibition by Adjunctive Cilostazol Versus High Maintenance-Dose Clopidogrel in Patients With Acute Myocardial Infarction According to Cytochrome P450 2C19 Genotype

Abstract: Compared with high-MD clopidogrel, adjunctive cilostazol significantly enhances platelet inhibition and reduces the rate of HPR, especially in AMI patients with CYP2C19 loss-of-function variants. (Adjunctive Cilostazol Versus High Maintenance-Dose Clopidogrel in Acute Myocardial Infarction (AMI) Patients According to CYP2C19 Polymorphism [ACCELAMI2C19]; NCT00915733).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 38 publications
0
31
0
Order By: Relevance
“…1). In this issue of JACC: Cardiovascular Interventions, the results of 3 independent investigations assessing these strategies among patients more prone to poorly metabolize clopidogrel based on the presence of CYP2C19 LOF alleles are reported and provide important insights on this ever-rising clinical quandary (5)(6)(7).…”
mentioning
confidence: 99%
“…1). In this issue of JACC: Cardiovascular Interventions, the results of 3 independent investigations assessing these strategies among patients more prone to poorly metabolize clopidogrel based on the presence of CYP2C19 LOF alleles are reported and provide important insights on this ever-rising clinical quandary (5)(6)(7).…”
mentioning
confidence: 99%
“…23 Recent studies showed that the addition of cilostazol to DAPT (i.e., triple antiplatelet therapy) resulted in greater ADP-induced platelet inhibition compared with DAPT. 24- 27 The present finding suggested that adjunctive cilostazol therapy could be an alternative regimen for achieving enhanced platelet inhibition in carriers of CYP2C19 reduced-function alleles.…”
Section: Discussionmentioning
confidence: 68%
“…14- 16 Compared with double-dose clopidogrel therapy (150 mg/day), TAPT was associated with a greater decrease in adenosine diphosphate (ADP)-induced platelet aggregation. 14, 15 The latter observation has been consistently observed in various high-risk clinical settings (ACS, diabetes, and complex PCI), including the carriage of the CYP2C19 loss-of-function allele. 15, 16 In addition, Yang et al 17 reported that platelets expressed the adenosine A2b receptor, which was upregulated under stress in vivo.…”
Section: Article P 2581mentioning
confidence: 87%